88 Feedlot performance and carcass traits of Nellore cattle fed virginiamycin to shorten the adaptation period to high-concentrate diets. (7th December 2018) - Rigueiro, A; Silvestre, A; Squizatti, M; Garcia, C; Estevam, D; Dias, E; Felizari, L; Demartini, B; Caixeta, E; Santi, P; Arrigoni, M; Millen, D
Abstract: This study, conducted at São Paulo University feedlot, Dracena, Brazil, was designed to evaluate the effects of feeding virginiamycin (VM), as sole feed additive, to shorten the adaptation period to high-concentrate diets on feedlot performance of Nellore cattle. The experiment was designed as a completely randomized block, replicated 6 times (4 animals/pen), in which 120 18-mo-old yearling Nellore bulls (394.5 ± 19.0 kg) were fed in 30 pens for 112-d according to the treatments: sodium monensin (MON) and 14-d adaptation period, MON plus VM and 14-d adaptation, VM and 14-d adaptation; VM and 9-d adaptation, and VM and 6-d adaptation. MON and VM were added into diets at 30 and 25 ppm, respectively (DM basis). Three adaptation diets were fed over periods of 14-d, 9-d or 6-d with concentrate level increasing from 69% to 84% (DM basis). Contrasts were used to assess linear and quadratic effects of adaptation length in cattle fed only VM, and differences between cattle fed VM and adapted for 14-d and those fed MON or MON+VM. No treatment effect was observed (P>0.10) for final BW, ADG, and HCW. As the adaptation period lasted longer, DMI in kg (MON: 9.74, MON+VM: 9.70, VM 6-d: 9.92, VM 9-d: 10.43, VM 14-d: 10.03) was affected (P=0.02) quadratically, and final back fat thickness in mm increased linearly (MON: 5.61, MON+VM: 6.26, VM 6-d: 4.87, VM 9-d: 5.60, VM 14-d: 5.99), in cattle fed only VM. Cattle fed MON or MON+VM had improved G:F when compared those fed VM and adapted for 14-d (MON: 0.149, MON+VM: 0.146, VM 6-d: 0.138, VM 9-d: 0.135, VM 14-d: 0.135). However, cattle fed MON+VM had a decreased dressing percentage when compared to cattle fed VM and adapted for 14-d (53.7% vs. 55.0%). Thus, adaptation period should not be shortened when VM is fed as sole feed additive.